A simple mass oscillator metasurface design with linear phase shift. (20th January 2022) - Wang, Wei; Xuan, Chengming; Xu, Weikai; Yang, Zhe; Li, Jie
Abstract: In this paper, a simple mass oscillator metasurface is designed, which can regulate the phase shift of flexural wave covering 0–2 π by adjusting the number of mass oscillators on the connecting bar. Based on the forced vibration theory, there is a simple approximately linear relationship between the number and phase shift of mass oscillators, which can more intuitively and accurately predict the phase of different number of mass oscillators, and then realize the metasurface design of mass oscillators with different requirements. Therefore, arbitrary regulation of flexural waves, such as abnormal refraction, beam focusing, and self-acceleration, can be realized by reasonably arranging the number of mass oscillators. The results show that the proposed metasurface can be greatly simplified both in the establishment of phase shift relation and in the fabrication of structure configuration, and will have broad application potential in the engineering field.